EU Electricity Policy (Im)balance: A Quantitative Analysis of Policy Priorities Since 1986 - Bostan, Mircea (Mike) (International Journal of Energy Economics and Policy, 2021)
The European Union has produced hundreds of laws in the field of electricity policy in the last three decades, on issues ranging from nuclear disposal to renewable energy generation support. Is the EU electricity policy of the last 30 years balanced, according to the classical energy trilemma framework? An all-inclusive, quantitative, multi-decade examination of the EU energy policy is still lacking. Besides the traditional policy perspectives, policy density and intensity, this paper proposes a novel method to measure policy outcomes: policy importance. The results show that EU energy legislation is indeed imbalanced. Environmental concerns rank first among EU electricity policy priorities; however, since 2003, the creation of an internal market has started to challenge environment as the top priority. Furthermore, internal market policies tend to have a higher trend of adoption than environment. Security of supply is at the bottom of EU policymakers’ attention. The EU energy policy is becoming more intricate, but not more revolutionary. Meaningful policy changes occur at a stagnating yearly rate, despite the increasing power of the EU institutions. Keywords: electricity policy; quantitative; policy density; policy intensity; European Union JEL Classifications: F530, Q480 DOI: https://doi.org/10.32479/ijeep.11461